Sinergi Seni, Budaya, dan Infrastruktur Berkelanjutan untuk Mitigasi Perubahan Iklim di Kabupaten Malang - Ahmad Dahri; Ita Suhermin Ingsih (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2025)
Climate change poses significant challenges to environmental sustainability and socio-cultural resilience, particularly in regions rich in local arts and cultural heritage. This study aims to analyze the role of local arts and culture in supporting sustainable infrastructure development as a climate change mitigation strategy. A qualitative descriptive approach was employed through literature review, policy document analysis, and examination of relevant previous studies. The findings indicate that local arts and culture effectively function as environmental communication media, public education tools, and mechanisms to strengthen community participation in the planning and maintenance of green infrastructure. The integration of local wisdom values into infrastructure design and implementation enhances environmental awareness, social acceptance, and long-term sustainability of development programs. Nevertheless, several challenges remain, including limited policy support, insufficient funding, and weak cross-sector collaboration. This study concludes that the synergy between arts, culture, and sustainable infrastructure represents a strategic and context-based approach to climate change mitigation, requiring strong policy frameworks and active community involvement.